Coordinated Regulation of Rsd and RMF for Simultaneous Hibernation of Transcription Apparatus and Translation Machinery in Stationary-Phase Escherichia coli - Yoshida, Hideji; Wada, Akira; Shimada, Tomohiro; Maki, Yasushi; Ishihama, Akira (Frontiers in Genetics, 2019)
Transcription and translation in growing phase of Escherichia coli, the best-studied model prokaryote, are coupled and regulated in coordinate fashion. Accordingly, the growth rate-dependent control of the synthesis of RNA polymerase (RNAP) core enzyme (the core component of transcription apparatus) and ribosomes (the core component of translation machinery) is tightly coordinated to keep the relative level of transcription apparatus and translation machinery constant for effective and efficient utilization of resources and energy. Upon entry into the stationary phase, transcription apparatus is modulated by replacing RNAP core-associated sigma (promoter recognition subunit) from growth-related RpoD to stationary phase-specific RpoS. The anti-sigma factor Rsd participates for the efficient replacement of sigma, and the unused RpoD is stored silent as Rsd-RpoD complex. On the other hand, functional 70S ribosome is transformed into inactive 100S dimer by two regulators, RMF (ribosome modulation factor) and HPF (hibernation promoting factor). In this review article, we overview how we found these factors and what we know about the molecular mechanisms for silencing transcription apparatus and translation machinery by these factors. In addition, we provide our recent findings of PS-TF (promoter-specific transcription factor) screening of the transcription factors involved in regulation of the rsd and rmf genes. Results altogether indicate the coordinated regulation of Rsd and RMF for simultaneous hibernation of transcription apparatus and translation machinery.